A case of Legionella pneumophila serogroup 13 pneumonia based on the detection of serogroup-specific genes in culture-negative sputum - Seto, Junji; Takahashi, Jun; Sampei, Mika; Ikeda, Tatsuya; Mizuta, Katsumi (Japanese Journal of Infectious Diseases, 2024)
Legionella pneumophila serogroup (SG) 1, the main cause of Legionnaires' disease, can be diagnosed with urinary antigen testing kits; however, lower respiratory tract specimen culture is necessary to identify L. pneumophila SG 2–15. We attempted to detect L. pneumophila SG-specific genes in a culture-negative sputum specimen from a patient with pneumonia suspected to have Legionnaires’ disease. Two multiplex PCR methods targeting L. pneumophila were modified and amplicons considered to be SG13 specific were detected. Direct sequencing revealed that the amplicons were identical to the nucleotide sequence of L. pneumophila SG13. Based on the presentation and clinical course (fever, muscle pain, disturbance of consciousness, high C-reactive protein titer, rhabdomyolysis, hypophosphatemia, and symptomatic improvement with levofloxacin treatment) in combination with the detection of L. pneumophila SG-specific genes, we suspected L. pneumophila SG13 pneumonia. L. pneumophila non-SG1 pneumonia is thought to be underestimated due to of its difficult laboratory diagnosis. The modified multiplex PCR system for lower respiratory tract specimens shown in this study is likely to increase the diagnosis of Legionnaires' disease caused by L. pneumophila SG13 and other SGs.